The embeddedness of responsible research innovation in Sabadell’s territorial policies: the case of smart specialization in industrial systems - Anastasios Andronikidis; Amalia Kouskoura; Eleni Kalliontzi; Ioannis Bakouros (Journal of Innovation and Entrepreneurship)
Abstract Purpose This paper aims to explore the integration of Responsible Research and Innovation (RRI) into Sabadell’s territorial policies, focusing on the development of an inclusive innovative ecosystem. Through various methodologies, the study seeks to enhance territorial specialization in design applied to industry within a sustainable framework. By embedding RRI principles, the objective is to foster a balanced approach that promotes social inclusion, sustainability, and economic growth in Sabadell's innovation landscape. Approach The study involves defining the policy and scientific objectives tailored to Sabadell’s territorial needs and reviewing relevant literature on strategies and measures that support policy advancement. A qualitative system analysis was conducted to identify key system elements serving as leverage points for embedding RRI and AIRR (Anticipation, Inclusiveness, Reflexivity, and Responsiveness) dimensions into Sabadell’s innovation ecosystem. This included assessing how each system element influences others, leading to the development of a system grid that highlights the most active and ambivalent elements crucial for advancing the city’s policy objectives. Additionally, stakeholder engagement was emphasized to ensure diverse perspectives were considered, promoting collaboration across sectors. The combination of literature review, system analysis, and impact assessment aims to create a robust, evidence-based framework for embedding RRI principles into Sabadell’s policies, fostering a more inclusive and sustainable innovation environment. Findings The qualitative system analysis identified 20 leverage points crucial for advancing Sabadell’s policy focus and embedding RRI/AIRR dimensions in the territory. These elements involve diverse stakeholders, including policymakers, industry leaders, academia, and civil society, ensuring a holistic approach. From these, 14 elements were selected based on their impact potential, forming the core drivers of policy advancement in Sabadell. These drivers will serve as a foundation for future actions aimed at strengthening Sabadell’s policy initiatives and embedding sustainable innovation practices across the territory. Originality This paper contributes to the ongoing discourse on embedding Responsible Research and Innovation into regional policies within a European context. By presenting Sabadell as a case study, it offers a practical model for integrating RRI into territorial strategies to build an inclusive, sustainable innovation ecosystem that enhances industrial specialization while addressing social and environmental challenges. The methodology provides a replicable framework for other regions aiming to align innovation policies with RRI principles.